Upaya guru dalam menghadapi sisiwa berkebutuhan khusus dalam film Taraa Zameen Par - Burmaizar, Anelda Ultavia; Rahmah, Anindita Ulya; Susilowati, Alifah; Arjelita, Arjelita; Riyanto, Arifin; Panghegar, Arowana Harries; Alfiani, Arum; Listiyaningrum, Arti; Anggraeni, Wahyu (Bulletin of Educational Management and Innovation, 2023)
Tara Zamen par is a film that tells the story of a child who has a little problem understanding learning, but the child really likes and is good at drawing and painting. But with a teacher who pays attention to the child and finds out about the child, finally the child can follow the learning in class well this. This study aims to reveal the efforts of teachers in dealing with students with special needs in the film Tara Semen Par. Research method used semiotic analysis. Semiotic analysis was used to uncover the symbols used in the film. These symbols are then interpreted as a teacher's effort in dealing with children with special needs in class. The results of the study found that the teacher's efforts in solving children's problems with special disorders were (1) analyzing the problems faced by children. (2) adjust to the child's learning style. (3) coordinate with parents to solve children's problems.